A Carbon Nanofiber Electrochemical Sensor Made of FeMn@C for the Rapid Detection of Tert-Butyl Hydroquinone in Edible Oil - Yan Xiao; Yi Zhang; Zhigui He; Liwen Zhang; Tongfei Wang; Tingfan Tang; Jiaxing Chen; Hao Cheng (Molecules)
Overuse of tert-butylhydroquinone (TBHQ) as a food antioxidant has the potential to pollute the environment and threaten human health. Therefore, it is imperative to develop precise and rapid methods to detect TBHQ in food products. In this study, Fe- and Mn-doped Prussian blue analogs (FeMn-PBAs) were prepared by co-precipitation, FeMn-PBAs/PAN was prepared by electrostatic spinning, and a novel FeMn@C/CNFs composite was prepared by carbonization in nitrogen. Bimetallic FeMn doping has been shown to reduce vacancy defects and enhance the structural stability of PBA. Furthermore, electrostatic spinning has been demonstrated to reduce the agglomeration of PBA nanoparticles, which are electrode-modifying materials with high stability and good electrical conductivity. The morphological and structural characteristics of the FeMn@C/CNF composites were examined using scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The electrochemical behavior of tert-butyl hydroquinone in FeMn@C/CNFs was studied by cyclic voltammetry (CV), differential pulse voltammetry (DPV), and chronocoulometry (CC). The results demonstrate that the sensor exhibits excellent repeatability, reproducibility, and anti-interference capabilities. The prepared electrochemical sensor can be effectively utilized for the detection of TBHQ in food samples such as soybean and peanut oil samples, proving its strong potential for practical applications.